Documenting and activating educational leadership and authentic teaching - Symbaluk, Diane; Andrews, David M.; Potter, Tiffany; Zecevic, Aleksandra (My University, 2024)
This essay describes two integrated projects initiated by the 2020 3M National Teaching Fellowship Award (NTF) cohort on educational leadership and the role of authenticity among exemplary teachers, as presented at STLHE 2022. A thematic analysis of 3M NTF award-winning dossiers identified six prevalent traits characteristic of educational leaders: innovation, persistence, responsiveness, reflectiveness, curiosity, and positive opportunism. The analysis also revealed aspects of educational leadership in practice, including being committed to a cause, being action-oriented, being community-engaged, being multi-disciplinary, building bridges, freely sharing, trailblazing, and using applied methods. Educational leaders’ relationships with others tended to foreground elements of collaboration, empowerment, support, and mentorship, and their actions had an impact beyond their own classrooms or institutions. In the second project, qualitative interviews with cohort members articulated ways in which authentic teaching is expressed by educational leaders. The actions of authentic teachers were viewed as influential and inspiring, and based on their actions authentic teachers tended to be recognized as instruments of change. These results were shared in an interactive workshop at STHLE 2022, which discussed how educational leadership is currently framed in higher education, and guided participants in self-reflection as educators and leaders to formulate calls to action involving educational leadership and authentic teaching.
Keywords: educational leadership; educational leaders; authentic teaching